The Role of Academic Ethics in the Professional Relationships of University Academic Staff - E. A. Popov (Высшее образование в России, 2024)
The subject of the research in the paper is academic ethics in the professional relationships of university teachers. The final results are presented on the basis of in-depth interviews with representatives of the academic staff of Russian universities (N=35). The purpose of the paper is to show how academic ethics as a value-normative phenomenon supports the professional relationships of academic staff at the university and forms certain values that ensure the effectiveness of the scientific and educational process. In this interpretation, the emphasis is placed on identifying the creative potential of academic ethics, its impact on the scientific and educational process at the university in terms of professional interaction of its main subjects. An assessment of the structure and content of academic ethics is given. It is established that academic ethics, being an element of academism in the higher education system, influences the formation of value-normative attitudes of respect and recognition. In addition, the importance of this phenomenon for the strategic development of the university and at the same time the preservation of academic traditions is revealed. The article also summarizes the assessments of the state of academic ethics at universities formulated by informants. In such assessments, value-semantic reflection prevails, which makes it possible to identify academic ethics as a factor of effective professional interaction between subjects of the educational process in order to achieve joint goals for the formation of their value world and professional knowledge and skills.